Self-rated health in Brazilian adults and elderly: Data from the National Household Sample Survey 2008. - Aparecida Höfelmann, Doroteia; Posenato Garcia, Leila; Santana de Freitas, Lúcia Rolim (Salud Pública de México)
Objective. To investigate prevalence of poor self-rated health and its association with individual and household-level characteristics among adults and elderly in Brazil. Materials and methods. Cross-sectional study with Brazilian National Household Sample Survey 2008 (n=257 816). Crude and multilevel-adjusted Poisson regression models were fitted. Results. After adjusted analysis, poor self-rated health was significantly associated with higher household income, living alone, not having piped water nor garbage collection, lower education, not having health insurance, female sex, higher age, being a current or previous smoker, physical inactivity, having chronic diseases, having physical impairment. Subjects living in rural areas also had higher prevalence of poor self-rated health. The factors most strongly associated with the outcome were physical impairment and reporting three or more chronic diseases. Conclusions. Socioeconomic, health related behaviors, and physical health were associated with poor self-rated health.